La importancia del proceso de Planificación de Negocio Integrado (IBP) sobre la rentabilidad en una empresa: caso Kimberly-Clark Perú - Bedoya Palacios, Renato (2022)
The objective of this work is to determine the importance of the process known as Integrated Business Planning (IBP) on business profitability. The research has a qualitative approach, descriptive and explanatory scope. The population comprised employees of the commercial area of the company Kimberly-Clark Peru, specifically executives and managers of the areas related to the process active in the payroll during the period 2020. The sample was 15 people and it was used as an instrument for collecting information about the structured interview. After an analysis of the sample and based on the existing theory about the process under study, it was possible to determine that there is a relationship between compliance with the IBP and the profitability of the company since the objectives of this process are mainly financial, such as reduction of inventories, the increase in service levels, the increase in cash-flow, supply capacity and the increase in the company's profit margin; They support the sustainable growth of the company and its areas. On the other hand, it was possible to conclude and assert the importance of this process in the company by describing the main characteristics immersed in the IBP and the variables related to the process and the areas involved in achieving a synergy between the supply chain and business profitability.